Urgensi Penanaman Sikap Moderasi Beragama Dalam Pendidikan Formal - Erika Fauziah (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Efforts to instill an attitude of religious moderation must be carried out from an early age in students by applying it to the educational process. In the process of Islamic religious education in educational institutions, the internalization of an attitude of religious moderation is an effort to prevent deviant and radical religious behavior for the Indonesian generation which can damage religious harmony in Indonesia and have an impact on the disintegration of the Indonesian nation. This journal tries to find answers about what is the concept of religious moderation? And the urgency and strategy of cultivating an attitude of moderation in play in formal education. This research is included in the type of library research, namely research that collects data from books, journals and previous research results that are relevant to the research subject using descriptive analysis methods. From this research, it is concluded that religious moderation is a just and balanced way of viewing (thinking), understanding and practicing (practice) religious life to create unity, oneness and peace as well as tolerance between religious communities which has an important urgency for all Indonesian citizens. So, in the realm of implementation it is certainly not limited to concepts or theories conveyed to students. But it must be done through practice or practice in everyday life.